THE RELATIONSHIP BETWEEN PASSENGER NUMBERS AND AIRCRAFT MOVEMENTS OF CHIANG MAI AIRPORT - Sangsomboon, Ploywarin; Jandaboue, Wanlapa; Vijitsanguan, Parnkan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The objectives of this study were to: 1) Analyze the correlation of statistical data between aircraft movements and passenger numbers of Chiangmai airport 2) Present the model of correlation between aircraft movements with passenger numbers of Chiangmai Airport. This research analyzed statistical data of Chiangmai airport operations from year 2010-2020 using simple linear regression analysis and the findings were by the correlation of statistical data between total aircraft movements and domestic passenger numbers, total aircraft movements and total passenger numbers, and total aircraft movements and international passenger numbers of Chiangmai international airport has (R2) 0.998, 0.996 and 0.936 consecutively that have correlation coefficient (R2) closet to 1. These are suitable to be used for futuristic airport planning and developing at Chiangmai Airport.